BIHS Harmonized Dataset - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
This dataset is was created by re-compiling available open, gender/sex-disaggregated Feed the Future datasets for Bangladesh and applying standard processing methods to enhance their accessibility and interoperability. This process entailed the standardization of variable names and labels, the creation of derived socio-economic indicators such as dietary diversity scores, household dependency ratios, and household age and gender composition. This dataset allows researchers to easily use data for Bangladesh, as well as make cross country comparisons with other standardized datasets. Moreover, the provision of household GIS coordinates (offset for confidentiality purposes) allows users to match data at different levels. This work combines multi-topic household and community socio-economic and agricultural surveys with biophysical datasets from multiple sources, including remote sensing, for a thorough comparison of different phenomena. These biophysical sources include the International Soil Reference and Information Centre (ISRIC) World Soil Information, NASA MODIS vegetation indices and land surface temperature data, and the HarvestChoice spatially-disaggregated subnational crop production statistics database (Spatial Production Allocation Model; SPAM).